HIV-1 Infection in Cyprus, the Eastern Mediterranean European Frontier: A Densely Sampled Transmission Dynamics Analysis from 1986 to 2012 - Pineda-Peña, Andrea Clemencia; Theys, Kristof; Stylianou, Dora C.; Demetriades, Ioannis; Puchhammer, Elisabeth; Vandamme, Anne Mieke; Aleksiev, Ivailo; Lepej, Snjezana Zidovec; Linka, Marek; Fonager, Jannik; Liitsola, Kirsi; Kaiser, Rolf; et al. (Nature Research, 2018)
Since HIV-1 treatment is increasingly considered an effective preventionstrategy, it is important to study local HIV-1 epidemics to formulate tailored preventionpolicies. The prevalence of HIV-1 in Cyprus was historically low until 2005. To investigatethe shift in epidemiological trends, we studied the transmission dynamics of HIV-1 in Cyprususing a densely sampled Cypriot HIV-1 transmission cohort that included 85 percent ofHIV-1-infected individuals linked to clinical care between 1986 and 2012 based on detailedclinical, epidemiological, behavioral and HIV-1 genetic information. Subtyping andtransmission cluster reconstruction were performed using maximum likelihood and Bayesianmethods, and the transmission chain network was linked to the clinical, epidemiological andbehavioral data. The results reveal that for the main HIV-1 subtype A1 and B sub-epidemics,young and drug-naïve HIV-1-infected individuals in Cyprus are driving the dynamics of thelocal HIV-1 epidemic. The results of this study provide a better understanding of thedynamics of the HIV-1 infection in Cyprus, which may impact the development of preventionstrategies. Furthermore, this methodology for analyzing densely sampled transmissiondynamics is applicable to other geographic regions to implement effective HIV-1 preventionstrategies in local settings.
Keywords: Adult; Cluster Analysis; Cyprus/epidemiology; Disease Transmission, Infectious; Female; Genotyping Techniques; HIV Infections/epidemiology; HIV-1/classification; Humans; Male; Middle Aged; Molecular Epidemiology; Prevalence; Young Adult; General; Research Support, Non-U.S. Gov't; Journal Article